Developing occupation kits in a Hand Therapy Student Experiential Learning Clinic. (June 2020) - Berlet, Logan; Kaskutas, Vicki
Introduction: Combining occupation-based and biomechanical approaches is effective to increase function after hand injury. This project developed and evaluated occupation kits as a means to increase occupation-based practice. Methods: Descriptive study that utilized existing Disabilities of the Arm, Shoulder and Hand data from 642 patients treated by hand surgeon and patients in our Hand Therapy Student Experiential Learning Clinic (HTSELC) to identify difficult activities. These data informed the selection of occupational areas to address with the kits. Biomechanical demands of each kit developed were quantified by 10 student therapists using the Abilities Questionnaire. Fourteen occupational therapists reviewed and rated the usefulness of each kit by survey. Kits were piloted in the HTSELC, and student therapists documented the percentage of time delivering each intervention type: activity/occupation, preparatory methods and tasks, education, advocacy, and group. The degree of occupation-based practice was compared using intervention type percentages before and after introduction of the kits. Results: Ten kits were created to address most occupation categories within occupational therapy's scope of practice. Kits include procedures, safety precautions, and a standardized scale to objectively measure performance. Clinicians noted that kits reflected each occupation well (3.7/5) and 45% reported they were likely to use the kits. After the kits became available in the HTSELC, the percentage of interventions at the occupation/activity level increased from 19% to 26% and biomechanical interventions, including preparatory methods and tasks, decreased from 61% to 49%. Conclusion: This research suggests that occupation kits can be a first step to help therapists deliver occupation-based interventions in hand therapy settings.